2022
DOI: 10.1002/jper.22-0065
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of periodontal status and cytokine levels in saliva and gingival crevicular fluid of patients with inflammatory bowel diseases

Abstract: In the presence of periodontal diseases in UC and CD, altered cytokine responses may be observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…Although a previous study showed higher salivary IL-1β and TNF-α levels in Crohn’s patients in comparison to systemically healthy controls, no information on the oral health status of the participants was given [ 28 ]. Indeed, similar to our findings, when the salivary samples were collected from individuals with healthy periodontium, no significant difference was observed in IL-1β, IL-10, IL-17A, and TNF-α levels between Crohn’s patients and healthy controls [ 29 ]. In inflammatory bowel disease patients, gingival and intestinal tissue Th17 cytokine expression profiles differ from each other [ 30 ], which indicates that the systemic condition is not the only determinant of oral cytokine expression, but the local environment, i.e., oral microbiome, also plays a significant role.…”
Section: Discussionsupporting
confidence: 88%
“…Although a previous study showed higher salivary IL-1β and TNF-α levels in Crohn’s patients in comparison to systemically healthy controls, no information on the oral health status of the participants was given [ 28 ]. Indeed, similar to our findings, when the salivary samples were collected from individuals with healthy periodontium, no significant difference was observed in IL-1β, IL-10, IL-17A, and TNF-α levels between Crohn’s patients and healthy controls [ 29 ]. In inflammatory bowel disease patients, gingival and intestinal tissue Th17 cytokine expression profiles differ from each other [ 30 ], which indicates that the systemic condition is not the only determinant of oral cytokine expression, but the local environment, i.e., oral microbiome, also plays a significant role.…”
Section: Discussionsupporting
confidence: 88%
“…The latter served as a contributor in the pathogenesis of periodontal disease, thus accounting for the occurrence of periodontitis in patients with UC ( 90 ). Another study similarly demonstrated an increase of IL-1β in the gingival crevicular fluid of patients with UC ( 91 ). In addition, Enver et al.…”
Section: Introductionmentioning
confidence: 81%
“…In addition, Enver et al. found that TNF-α levels were significantly higher in the saliva of patients with UC diagnosed with periodontitis, along with a reduction of IL-10 levels ( 91 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acharya et al showed a positive correlation between IL-6 and BOP%, suggesting a strong proinflammatory effect that enhances alveolar bone destruction and affects vascular homeostasis [53] . Studies by Enver et al, Gündoğar et al, and Al-Hamoudi et al have also revealed that IL-1β levels increase and IL-10 levels decrease in the presence of periodontitis, leading to dysregulation of the expression of inflammatory cytokines [54][55][56] . Hoare et al and Bakhsh et al have reported an increase in the mRNA levels of IL-1β, IL-6, and IL-8 in gingival tissue samples [57,58] .…”
Section: Discussionmentioning
confidence: 97%